2021
DOI: 10.1007/s10695-021-01029-1
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol and Lippia alba essential oils as effective anesthetics for the Amazonian freshwater stingray Potamotrygon wallacei (Chondrichthyes, Potamotrygonidae)

Abstract: This study assessed the potential of eugenol and the essential oil of Lippia alba (EOLA) in providing suitable anesthetic induction and recovery times, and their consequent effects on the blood and respiratory physiology, as well as the gill architecture of an Amazonian freshwater stingray, Potamotrygon wallacei, at the onset of the anesthetic event and after 48 h of recovery. Juveniles of P.wallacei (n = 12) were exposed to increasing concentrations of eugenol (75, 100, 125 and 150 µL L − 1 ) and EOLA (150, 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In some studies, extensive histopathological abnormalities were observed in the gill, including hyperplasia, epithelial lifting, and curling of lamellae after exposure to anesthetics (essential oils of A. triphylla, L. sidoides, and M. piperita, MS-222, eugenol), indicating that the gill is a sensitive organ for responding to anesthetics (Brandão et al, 2021;Wang et al, 2020;Lima et al, 2021). In the present study, changes in gill morphology were identi ed using H&E staining and were classi ed in three degrees, according to de Lima et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, extensive histopathological abnormalities were observed in the gill, including hyperplasia, epithelial lifting, and curling of lamellae after exposure to anesthetics (essential oils of A. triphylla, L. sidoides, and M. piperita, MS-222, eugenol), indicating that the gill is a sensitive organ for responding to anesthetics (Brandão et al, 2021;Wang et al, 2020;Lima et al, 2021). In the present study, changes in gill morphology were identi ed using H&E staining and were classi ed in three degrees, according to de Lima et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yigit and Kocaayan ( 2023 ) reported that thyme essential oil caused marked hyperemia, oedema, inflammatory cell infiltrations and desquamation in gills. de Lima et al ( 2021 ) also reported that eugenol caused moderate to severe histological changes in the gills of the Amazonian freshwater stingray, Potamotrygon wallacei . Brandão et al ( 2021 ) reported hypertrophy and hyperplasia of the lamellar epithelium, lamellar fusion and proliferation of chloride cells in Colossoma macropomum anaesthetized with essential oils of Aloysia triphylla , Lippia sidoides and Mentha piperita .…”
Section: Discussionmentioning
confidence: 96%
“…The carp were randomly divided into 27 treatment groups and a blank group, with 10 carp in each group. The carp were then immersed individually in a solution of 75 mg/L of eugenol for 15 min, and the medicine bath administration was performed according to the literature ( 19 , 20 ). The appropriate eugenol was first diluted in ethanol (1:10, v/v) and then added to water to keep the immersion concentration of eugenol at 20, 35, and 75 mg/L.…”
Section: Methodsmentioning
confidence: 99%